Toleransi Sosial Keberagamaan pada Masa Nabi Muhammad SAW dan Relevansinya dalam Pengembangan Masyarakat Majemuk di Indonesia - Budimansyah, Budimansyah; HS., MA. Achlami; Safari, Safari (Analisis: Jurnal Studi Keislaman, 2023)
Muslims recognize the right to "existence" (not "truth") of other religions based on the principles of religious freedom and a tolerant attitude towards other religious communities. Discussions about religious tolerance are an interesting object of study. This is because apart from the operational details in the Qur'an and hadith, this attitude was practiced directly by the Prophet Muhammad during his lifetime. On this basis, this article attempts to analyze the attitude of social religious tolerance during the time of the Prophet Muhammad SAW and is related to religious tolerance in Indonesia. This study is descriptive qualitative literature research using a historical and sociological approach to religion, while the analysis used is content analysis and comparative methods. The results of this study show that the principles of social and religious tolerance practiced by the Prophet Muhammad SAW in the city of Medina have implications and shared values in terms of the diversity of Indonesian society. Religious social tolerance can be used as an alternative model in developing a pluralistic society in Indonesia.